Notes on Helix pomatia (L.) feeding in commerciai breeding (Bollettino di zoologia agraria e bachicoltura, 2024)
Helix pomatia is the object of intensive breeding for use in the canned food industry and for direct consumption in delicatessen shops.This paper is concerned with the feeding of molluscs which is only one of the numerous problems related to the management of breeding parks. Numerous tests have beem performed for comparison of body weight increase and mortality rates in the groups fed plain or associated vegetables or vegetables integrated with different substances, using 10 samples of 50 one year old snail fed respectively for 3 months on: Petasites officinalis, Urtica urens, Cichorium intybus and Solidago virga-aurea, C. intybus with alfalfa and flour pellets, Arctium lappa with wheat bran, Cucurbita maxima leaves, Cucurbita maxima fruit with maize flour, C. maxima fruit with wheat bran, Beta vulgaris. At the end of our testing the mean body weight gain and mortality rate weremeasured and observations were made on the egg laying and survival of littlesnails. The authors could conclude that some plants gave better results in relationto the weight gain and mortality rate of adult snails (Arctium lappa, Cichoriumintybus, Urtica urens) while other plants are most necessary to create thesuitable habitat for the development of little and adult snails (Petasites officinalis,U. urens): the associated culture of these species, integrated with pre-preparedfeeds (pellets of alfalfa flour, wheat bran and ·maize flour) are the key tosuccessful molluscs breeding.